Physical activity is associated with low-level stress among a sample of seniors during COVID-19 outbreak? - Chellsea Hortêncio Alcântara; Rafael Martins da Costa; Elorides de Brito; Maira Mendes dos Santos Marques; Euler Esteves Ribeiro; Elisa Brosina de Leon (Revista Brasileira de Atividade Física e Saúde)
This study aimed to verify the association of physical activity, behaviors, and health conditions with stress among a sample of older adults from Manaus, Brazil, during the COVID-19 outbreak. This is a cross-sectional analysis of 79 older adults (76% female; age: 68.24 ± 6.82 years) from Fundação Universidade Aberta da Terceira Idade (FUnATI). The perceived stress (PS) was assessed by the Perceived Stress Scale, while a questionnaire via telephone call. The variables also included physical activity, sleep quality, sociodemographic, and health condition variables. Linear Bayesian mixed-effects regression models were applied to verify the association between these correlates with PS. Older people who met the recommendations before the COVID-19 outbreak but did not meet the same recommendations during the COVID-19 outbreak have a higher PS score compared to those older people who did not meet the PA recommendations at either time. In contrast, those elderly people who met PA recommendations before and during the COVID-19 outbreak had a lower PS score compared to their peers who did not meet physical activity recommendations at either time. Those older people who did not meet the PA recommendations before the COVID-19 outbreak, but did meet the PA recommendations during the COVID-19 outbreak, did not have significant differences in the PS score compared to their peers who did not meet the PA recommendations in either moment. Sleep changes and high BMI were negatively associated with PS. The maintenance of physical activity during the pandemic was associated with lower levels of stress in older people.